Prevalence of Metabolic Syndrome and its Associated Factors Among the Employees of a Commercial Company in Togo - HINSON, Antoine Vikkey; KPATA, SEDJRO; Wognin, Barthélémy Sangah; MIKPONHOUE, ROSE; ADJOBIME, MENONLI; AYELO, Ahoumènou Paul; FAYOMI, EBOUM BENJAMIN (My University, 2017)
Background The Metabolic Syndrome is a set of clinical and biological signs that indicate a metabolic disorder and predispose to or indicate cardiovascular disease and/or type2 diabetes. Aims To evaluate the prevalence of metabolic syndrome and the associated factors among the employees of a commercial entity. Materials and Methods It was a cross-sectional descriptive study. The study population consisted of all employees who participated in the periodic medical examination in 2016.The metabolic syndrome was studied on the basis of the definition criteria of the FID-2005.Data analysis was performed using the Epi info software version 3.5.4. The chi-square test is used to compare the percentages. The logistic regression was used to analyze the relationship between metabolic syndrome and risks factors. The threshold of significance was p≤0.05. Results A total of 652 employees participated in our study. The prevalence of the metabolic syndrome was 26.5% according to the definition of IDF-2005. The presence of metabolic syndrome was significantly associated with other definitional criteria in addition to abdominal obesity: general obesity (44.4%), hypertension (31.0%), hyperglycemia (19.8%), HDL cholesterol (30.5%), and hypertriglyceridemia (15.2%). Among those criteria, the most frequent combinations included, besides abdominal obesity, low HDL cholesterol and a high blood sugar. In this company, more than 40 years old, work experience of 15 years or more, absence of high-energy physical activity, socio-professional groups of executives and executing agents were the risk factors significantly associated with the presence of the metabolic syndrome. Conclusion Metabolic Syndrome is a reality in the workplace in Sub-Saharan Africa. Adequate preventive measures must be taken.
Keywords: Metabolic Syndrome; Workers; Sub-Saharan; Africa; Togo